2011
DOI: 10.1007/s11409-011-9075-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring strategic processing when students read multiple texts

Abstract: This study explored the dimensionality of multiple-text comprehension strategies in a sample of 216 Norwegian education undergraduates who read seven separate texts on a science topic and immediately afterwards responded to a self-report inventory focusing on strategic multiple-text processing in that specific task context. Two dimensions were identified through factor analysis: one concerning the accumulation of pieces of information from the different texts and one concerning cross-text elaboration. In a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 46 publications
(74 reference statements)
3
49
1
8
Order By: Relevance
“…There are also issues with the generalized nature of the MARSI directions: students use strategies to a different extent in different contexts, even in academic reading, and context-free measures do not accurately reflect strategy use for all of those contexts (e.g., Bråten & Strømsø, 2011;Hadwin, Winne, Stockley, Nesbit, & Woszczyna, 2001;Pressley, 2000;Veenman, 2011). However, contextualizing the instrument to focus on specific readings would necessarily limit its generalizability.…”
Section: Validity Of the Marsimentioning
confidence: 99%
“…There are also issues with the generalized nature of the MARSI directions: students use strategies to a different extent in different contexts, even in academic reading, and context-free measures do not accurately reflect strategy use for all of those contexts (e.g., Bråten & Strømsø, 2011;Hadwin, Winne, Stockley, Nesbit, & Woszczyna, 2001;Pressley, 2000;Veenman, 2011). However, contextualizing the instrument to focus on specific readings would necessarily limit its generalizability.…”
Section: Validity Of the Marsimentioning
confidence: 99%
“…Bråten and colleagues investigated the relation between comprehension and repetition as well as between comprehension and elaboration. They assessed strategy use by analyzing note taking (Hagen, Strømsø, & Bråten, 2009) and a task-specific self-report inventory (Bråten & Strømsø, 2011). The results of their study indicated that integration strategies showed positive effects, whereas repeating factual information from single documents had negative effects on comprehension.…”
mentioning
confidence: 99%
“…Sin embargo, también requiere un ejercicio metacognitivo, sensible al contexto, autorregulado, disciplinado, orientado a la resolución de problemas y a la generación de conocimiento (Spicer y Hanks, 1995;Ennis, 1996;Lipman, 1998;Pinzás 2006). Además, son necesarias habilidades de lectura cruzada, en donde se encuentre coincidencias, se compare, se aplique, se identifique la forma en que está presentada la información, y se analicen las contradicciones y las coincidencias de la información (Bråten y Strømsø, 2011).…”
Section: Discusión Y Conclusionesunclassified
“…En cuanto a la evaluación del uso de estrategias de lectura hipertextual, los instrumentos de medición son limitados (Bråten y Strømsø, 2011), por lo que los indicadores en este trabajo pueden considerarse una contribución en esta área del conocimiento. La diferencia con los autores mencionados reside en que la medición de los ítems la efectuaron a partir de un caso en concreto y con la estrategia de "pensar en voz alta" (Thinking aloud) como un trabajo intenso en el aula.…”
Section: Discusión Y Conclusionesunclassified